The Arctic voyages of Martin Frobisher : an Elizabethan adventure - McGhee, Robert (University of Washington Press, 2001)
"Using reports from the men who participated in the venture, details preserved in the oral histories of the Inuit, and archaeological information recovered from the sites of Elizabethan activities on Baffin Island, Robert McGhee describes Frobisher's expeditions and offers new insights into this audacious undertaking. How could Martin Frobisher have convinced himself that a narrow bay on the coast of Baffin Island was a northwest passage to the Pacific? What became of the five members of his company who went ashore and were never seen again? What role, if any, did Frobisher play in the gold-mining fraud? Some of these questions may never be answered but, despite apparent failure, Martin Frobisher's ventures launched England's long period of intense exploration and discovery in this land."--Jacket.